Effect of renal interstitial vascular lesions on clinical pathological features and outcomes of lupus nephritis - HU Ai-xia; LIU Tao (Linchuang shenzangbing zazhi)
Objective To analyze the significance of renal interstitial vascular lesions in clinical treatment of lupus nephritis(LN). Methods Fifty-one patients diagnosed with LN through clinical manifestations and renal biopsy from January of 2010 to December of 2015 were divided into two groups into vascular lesion group and non-lesion group according to whether there is vascular lesions under a microscope. Retrospective analysis was performed; the clinical, laboratory, pathological manifestations and outcomes were compared between the two groups. Results Among the 51 patients, 9 ones were male(17.6%) and 42 ones were female(82.4%), with a mean age of(33.9±11.0), and a mean onset age of(31.3 ±11.3). Systemic lupus erythematosus course was 23(0.5-156) months, LN course was 3(0.1-144) months. In the vascular lesion group, chronic renal failure rate in the vascular lesion group was significantly higher than that in the non-lesion group(P=0.001); anemia was more obvious(P=0.003), serum creatinine was higher(P=0.003), and the estimated glomerular filtration rate was significantly lower(P=0.001); the positive rate of ds-DNA was higher(P=0.047).; the proportion of platinum loop in renal biopsy was significantly higher than that in non-lesion group(P=0.001); renal interstitial infiltration cell score(P=0.037), chronic lesion score(P=0.037) and chronic renal tissue index(CI)(P=0.014) were all higher than those in the non-lesion group. Conclusions The LN patients with renal interstitial vascular lesions have more obvious damage, and renal biopsy shows lupus activity is more obvious, chronic lesions are more serious, and long-term renal prognosis is poor.